2012
DOI: 10.1007/s12072-012-9361-8
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of interleukin-10RB to chronic hepatitis B virus infection and biological activities of interferon-λ and interleukin-22

Abstract: PurposeThe association of a single nucleotide polymorphism of interleukin (IL)-10RB codon 47 with the chronic hepatitis B virus (HBV) infection has been reported in two ethnic populations with different results, but not in a Korean population. IL-10RB is a subunit of receptor complexes for interferon-lambda (IFN-λ) and IL-22, which have antiviral and hepatocyte-protective activity, respectively. This study examined the association of IL-10RB K47E with the outcomes of HBV infection in Korean subjects and the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The HCA is a rapid viral molecular diagnostic method in which the specific single-stranded RNA probe is directly hybridized with denatured complementary DNA (cDNA) sequence as the target nucleic acid in a clinical sample. The HCA is used for detecting and identifying HBV and HCV ( Table 1 ) ( 5 , 35 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…The HCA is a rapid viral molecular diagnostic method in which the specific single-stranded RNA probe is directly hybridized with denatured complementary DNA (cDNA) sequence as the target nucleic acid in a clinical sample. The HCA is used for detecting and identifying HBV and HCV ( Table 1 ) ( 5 , 35 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…56 Cho's experimental results showed that IL10RB possibly caused chronic hepatitis B because cytokines combined with IL10RB can affect hepatocellular disease by regulating immune cells. 57 IFNL3 influences the severity of liver inflammation and fibrosis in viral and nonviral liver diseases. 58 In Figure 4F, those HBCD targets with d s = 1 in the overlap network, such as AR, MAPK1, and MAPK14, could regulate CEBPB to affect IL10, then IL10RB and IFNL3 could be mediated by IL10.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cytokine IL10RB could lead to liver fibrosis while it is differentially expressed in the nonalcoholic steatohepatitis adipose tissue . Cho’s experimental results showed that IL10RB possibly caused chronic hepatitis B because cytokines combined with IL10RB can affect hepatocellular disease by regulating immune cells . IFNL3 influences the severity of liver inflammation and fibrosis in viral and nonviral liver diseases .…”
Section: Discussionmentioning
confidence: 99%
“…IFN-α, which is expressed during viral infections, upregulates IL-22α on keratinocytes. In this context, IL-22 inhibits the differentiation of keratinocytes and increases the thickness of the epidermis, thereby mediating innate immune defense against viral infection [ 30 , 31 ]. In addition, the expression of IL-22Rα is significantly increased in the epidermis of patients with psoriasis [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%